SANKSI PIDANA PERJUDIAN ATAU JARIMAH MAISIR BERDASARKAN QANUN PEMERINTAH ACEH NO. 6 TAHUN 2014 TENTANG HUKUM JINAYAT (PUTUSAN MAHKAMAH SYARI’YAH SINABANG NOMOR 6/JN/2021/MS.SNB): Criminal Sanctions For Gambling Or Jarimah Maisir Based On Aceh Government Qanun No. 6 Of 2014 Concerning Jinayat Law (Syari'yah Court Ruling Sinabang Number 6/jn/2021/ms.snb) - Mulyansyah, Muhammad Riza; Susetyo, Heru (Faculty of Law, Universitas Trisakti, 2024)
The main issues raised are 1.) How is gambling regulated in Islamic law? 2.) How do maisir/gambling regulations compare in the Aceh Qanun and national law? This research uses a type of normative legal research which is descriptive analytical in nature using secondary data obtained through literature study and the data is processed qualitatively using deductive logical conclusions. The author's conclusion is that 1.) The regulation of gambling or Maisir in Islamic law is found in the Al-Quran, Surah Al-Baqarah verse 219 and Surah Al-Ma'idah verses 90-91. Supported by Ahmad, Laits, Ishak, and other adherents of the Shafi'i madzab, it is prohibited to be caned more than ten times if the sanction for the crime committed does not reach the sanction for adultery or theft does not reach the provisions for cutting off one's hand. 2.) The most striking thing in the comparison of the Aceh Qanun and National Law is the sanctions. In the regulation of the Aceh Qanun the criminal sanction for gambling is public caning, while the sanction for gambling in the National Law is imprisonment